An HPLC-ELSD Method for the Determination of Triterpenes in Sorbus decora and Sorbus americana Bark Used by the Eeyou Istchee Cree First Nation - Saleem, Ammar; Liu, Rui; Guerrero-Analco, José A.; Bailie, Anna; Foster, Brian; Cuerrier, Alain; Johns, Timothy; Haddad, Pierre S.; Arnason, John Thor (Planta Medica, 2016)
Sorbus decora and Sorbus americana are used traditionally as medicine by the Eeyou Istchee Cree First Nation of the James Bay region of Quebec, Canada. Because the ethanol extracts of the bark and the isolated terpenes of these plants have shown promising in vivo antidiabetic effects, an analytical method was developed and validated by RP-HPLC-ELSD for the identification and quantification of eight lupane- and ursane-type terpenes. The extraction method reproducibly recovered the compounds above 70 % and the chromatographic separation of betulin, 23-hydroxy-betulin, 23,28-dihydroxylupan-20(29)-ene-3β-caffeate, betulinic acid, α-amyrin, uvaol, 3β,23,28-trihydroxy-12-ursene, and 23,28-dihydroxyursan-12-ene-3β-caffeate was achieved within 27 min by linear gradient. The method produced highly reproducible quantitative data at interday and intraday levels. The limits of detection were in the ng level on-column with remarkable range and linearity. The target compounds were present at mg levels in the populations, collected from inland (Mistissini and Nemaska) and costal (Waskagnish and Chisasibi) Cree communities of northern Quebec. A triterpene, 23-hydroxybetulin, was the most abundant, while betulinic acid and uvaol were minor constituents. Overall, HPLC-ELSD analyses produced very similar profiles and contents of the eight compounds in the plants collected from four geographic locations. The developed HPLC-ELSD method can be used as a targeted analysis of triterpenes in these medicinal plants.
Keywords: Sorbus decora; Sorbus americana; Rosaceae; RP-HPLC-ELSD; triterpenes; Cree